2023
DOI: 10.1002/mde.3847
|View full text |Cite
|
Sign up to set email alerts
|

Horizontal and vertical demand forecast information sharing in a distributive dual‐channel supply chain considering the manufacturer's product quality improvement

Abstract: Under the influence of market demand uncertainty, we discuss the issue of horizontal and vertical demand forecast information‐sharing in a distributive dual‐channel supply chain composed of a manufacturer, a traditional retailer and an online retailer in which both retailers obtain heterogeneous demand information through big data technology. We analyze vertical information‐sharing strategies in the condition that the manufacturer invests in product quality improvement under different horizontal information‐sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 59 publications
(85 reference statements)
0
2
0
Order By: Relevance
“…Likewise, Yang et al (2020) found that the influence of online reviews could effectively increase the sales price of the manufacturer and the retailer's channel in the dual channel. The introduction of online commentary increases information sharing and reduces the impact of uncertainty in market demand, which benefits both members of the supply chain (Dou et al, 2023). If manufacturers open online channels and invest in online review services at the same time, they can effectively increase the selling price of manufacturers and retailers in dual channels (Yang et al, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, Yang et al (2020) found that the influence of online reviews could effectively increase the sales price of the manufacturer and the retailer's channel in the dual channel. The introduction of online commentary increases information sharing and reduces the impact of uncertainty in market demand, which benefits both members of the supply chain (Dou et al, 2023). If manufacturers open online channels and invest in online review services at the same time, they can effectively increase the selling price of manufacturers and retailers in dual channels (Yang et al, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…If manufacturers open online channels and invest in online review services at the same time, they can effectively increase the selling price of manufacturers and retailers in dual channels (Yang et al, 2020). Because the introduction of online reviews increases information sharing and reduces the impact of market demand uncertainty, this is beneficial for supply chain pricing (Dou et al, 2023).…”
Section: Pricing Decisionsmentioning
confidence: 99%